2003
DOI: 10.1128/jcm.41.7.3233-3240.2003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment by Meta-Analysis of PCR for Diagnosis of Smear-Negative Pulmonary Tuberculosis

Abstract: We conducted a meta-analysis to assess the performance of PCR for the diagnosis of smear-negative pulmonary tuberculosis (SPT) and to identify factors that account for differences in the diagnostic accuracy of different studies. Studies published before February 2002 were included if sensitivity and specificity of PCR in smear-negative respiratory or gastric-aspirate specimens could be calculated. Analysis was conducted by using summary receiver operating characteristics models. Sensitivity and specificity ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
3
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 60 publications
11
119
3
15
Order By: Relevance
“…A total of ten eligible studies (in English) were identified [12][13][14][15][16][17][18][19][20][21]. To this list, we added two meta-analyses published as abstracts [22,23].…”
Section: For Reprint Orders Please Contact Reprints@future-drugscommentioning
confidence: 99%
“…A total of ten eligible studies (in English) were identified [12][13][14][15][16][17][18][19][20][21]. To this list, we added two meta-analyses published as abstracts [22,23].…”
Section: For Reprint Orders Please Contact Reprints@future-drugscommentioning
confidence: 99%
“…No obstante, dado que aproximadamente entre el 20 y el 50 % de los pacientes con tuberculosis pulmonar son negativos a la baciloscopia y el 10 % de estos son negativos también al cultivo (20) se observa la necesidad de incorporar métodos diagnósticos más sensibles y de caracterización molecular de los aislados (21,22), lo cual permitiría la realización de un diagnostico rápido, una intervención oportuna y precisa. Así mismo, el empleo de estos métodos moleculares permite generar información epidemiológica de gran aplicación al momento de diseñar nuevas estrategias locales y regionales mejorando la efectividad de los programas de control.…”
Section: Discussionunclassified
“…No entanto, uma recente meta-análise demonstrou que a dosagem de ADA seria mais efetiva em termos de custo do que a dosagem de interferon-γ para o diagnóstico de TB. (23) Por esses motivos, não recomendamos o uso rotineiro do interferon-γ na prá-tica clínica atual.…”
Section: Marcadores Moleculares (Interferon)unclassified
“…(23) Um estudo avaliando o rendimento da reação em cadeia da polimerase no líquido pleural de 111 pacientes (57 com TB pleural) mostrou sensibilidade de 17% e especificidade 98%. (24) Além disso, as técnicas de amplificação de seqüên-cias de ácidos nucléicos ainda não foram validadas para uso em amostras não respiratórias como o líquido pleural.…”
Section: Marcadores Genéticosunclassified